Case 3370: Akeridae, Bithyniidae and Hydrobiidae (Mollusca, Gastropoda): proposed correction of authorship and date to Férussac, 1822, Gray in Turton, 1857, and Stimpson, 1865 respectively. - Kadolsky, Dietrich (Bulletin of Zoological Nomenclature, 2009)
Closed in BZN 76 (30 April 2019): 97
Keywords: Nomenclature; taxonomy; Gastropoda; Bivalvia; ACERIDAE; AKERIDAE; BITHYNIIDAE; Hydrobiidae; MARGARITIFERIDAE; Acera; Akera; Balcis; Eucampe; Margaritifera; Ocenebra; Eucampe donovani; Akera bullata; gastropods; bivalves